2021
DOI: 10.3389/fmicb.2021.706772
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Alters the Intestinal Microbiota and Metabolomic Profiles in Mice

Abstract: BackgroundHeat stress has negative effects on the intestinal health of humans and animals. However, the impact of heat stress on intestinal microbial and metabolic changes remains elusive. Here, we investigated the cecal microbial and metabolic profiles in mice in response to heat stress.MethodsThe mouse heat stress model was constructed by simulating a high-temperature environment. Twenty mice were randomly assigned to two groups, the control group (CON, 25°C) and the heat treatment group (HS, 40°C from 13:00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 79 publications
2
23
0
Order By: Relevance
“…Several transporters promoting UA secretion have been identified in the intestine (6). Gut microbiota and its metabolites have been proven to directly or indirectly participate in the metabolism of purine and UA (7)(8)(9). The complex interactions between intestinal microbiota and the host provide crucial insight into the pathogenesis of many inflammatory diseases including gout (5,10).…”
Section: Introductionmentioning
confidence: 99%
“…Several transporters promoting UA secretion have been identified in the intestine (6). Gut microbiota and its metabolites have been proven to directly or indirectly participate in the metabolism of purine and UA (7)(8)(9). The complex interactions between intestinal microbiota and the host provide crucial insight into the pathogenesis of many inflammatory diseases including gout (5,10).…”
Section: Introductionmentioning
confidence: 99%
“…Metabonomics is a technique for identifying and quantifying all metabolites present in biological samples. At present, Tang et al (2021) used non-targeted metabonomics to reveal the intestinal pathogenesis and self-healing of rabbits without antibiotic diet, He et al (2019a) used fecal metabonomics technology to explore the metabolic changes of heat stress in late pregnancy of primiparous sows, and Wen et al (2021) used metabonomics technology to explore the metabolic changes of heat stress on cecal contents of mice. However, the research on the relationship between heat stress and rabbit intestinal microbial ecosystem and its metabolites is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…After 14 d of heat stress treatment, opportunistic pathogens such as Campylobacterales , Veillonellaceae , and Megasphaera substantially increase ( Hu et al., 2020 ). On the other hand, we also found some probiotics, such as segmented filamentous bacteria and L. murinus , were diminished in heat stressed mice ( Wen et al., 2021 ). After applying fecal microbiota transplantation from heat-stressed pigs to mice, it was found that Bacteroides was significantly reduced while Akkermansia was significantly augmented ( Hu et al., 2020 ).…”
Section: The Negative Effect Of Heat Stress On Human and Animal Healthmentioning
confidence: 72%
“…The high temperature environment alters microbiota metabolism. The ambient environment mainly affects the homeostasis of carbohydrates, lipids, and amino acid metabolism in microbiota ( Chen et al., 2018 ; Cui et al., 2019 ; Tian et al., 2015 ; Wen et al., 2021 ; Zhong et al., 2019 ; Zhu et al., 2019 ), resulting in a higher expression of the environmental adaptation signaling pathway and immune-related pathway ( Chen et al., 2018 ). Different microbiota in spring and summer were mainly concentrated in the functions associated with infectious diseases, immune system diseases, and lipid metabolism in dairy cows ( Li et al., 2020 ).…”
Section: The Negative Effect Of Heat Stress On Human and Animal Healthmentioning
confidence: 99%
See 1 more Smart Citation